Republic of Tajikistan : Sixth Review Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Tajikistan. (IMF Staff Country Reports; Country Report, 2006)
This paper focuses on Tajikistan's Sixth Review Under the Poverty Reduction and Growth Facility (PRGF). The program for 2005 has been implemented satisfactorily. All quantitative and structural performance criteria and indicative targets for end-September 2005 were observed, and all outstanding structural benchmarks for 2005 have either been completed or are in the process of implementation. In view of the authorities' satisfactory implementation of the program during 2005, the IMF staff is recommending completion of the sixth review under the PRGF.